Combined Adjustment Pipeline for Improved Global Geopositioning Accuracy of Optical Satellite Imagery With the Aid of SAR and GLAS - Yong-Hua Jiang; Shaodong Wei; Miaozhong Xu; Guo Zhang; Jing-Yin Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
Owing to the widespread availability of multiple remote sensing methods, regions are often covered by satellite observation from multiple sources. However, the geometric positioning accuracy of optical satellites, which is the most common data source, is generally insufficient. An intuitive idea to improve accuracy is to integrate the dominant accuracy of multisource information. Previous articles have used synthetic aperture radar (SAR) and geoscience laser altimetry system (GLAS) data with improved geopositioning accuracy. However, the accuracy and applicability of existing combination methods are unsatisfactory because of various restrictions. In this article, a pipeline with automatic extraction of tie points and combined adjustment was designed based on nonstereo SAR images and GLAS data, considering both the high precision and wide distribution of multisource data. Experiments using real satellite data (ZY-3, GF-7, GF-3, and ICESat-2) and test areas covering complex landforms demonstrated the feasibility and effectiveness of the proposed pipeline. The geopositioning accuracy in three experimental areas reached 3.16, 3.36, and 3.17 m in the horizontal direction and 1.45, 1.25, and 1.28 m in the vertical direction. Our pipeline not only permits high accuracy close to the nominal accuracy of heterogeneous reference data but can also be extended to global high-precision geopositioning without ground control.